Design and validation of an instrument for the internationalization of SMEs, based on the Uppsala model and dynamic capacities - Rave-Gómez, Elkin Darío (2023)
SMBs have been crucial to the Colombian economy thanks to their contribution to job creation and their positive impact on production. Thus, this research aimed to identify the key categories and variables that influence SMB internationalization, based on the Uppsala model and the theory of dynamic capabilities. The methodology followed was structural equation modeling. The sample included 100 SMBs of the textile-dressmaking sector, geographically located around the city of Medellín, Colombia, in Valle de Aburrá. To define the theoretical relationships, among categories, variables, and hypotheses, was created a path diagram as a strategy to better observe causal relationships between dependent and independent variables. To determine the instrument’s reliability, we analyzed the data using SPSS and then ran the structural equations on the LISREL software. The results allowed us to identify the most appropriate categories and variables of the Uppsala model and the dynamic capabilities to be included in the multivariate model and determine which of them have a greater influence on SMB internationalization. In conclusion, the main findings suggest that the categories that can significantly impact the SMB internationalization process are Information (seven variables), Resources (eight variables), and Dynamic Capabilities (eight variables).